Large-area growth of high-quality graphene/MoS2 vertical heterostructures by chemical vapor deposition with nucleation control - Nguyen, Van Tu; Kim, Young Chul; Ahn, Yeong Hwan; Lee, Soonil; Park, Ji Yong (Carbon, 2020)
Vertical heterostructures of graphene and MoS2 are realized by successive growth of MoS2 and graphene, each by chemical vapor deposition. The MoS2 coverage on graphene is controlled by ozone treatment of graphene, which affects the absorption and aggregation of the nucleation promoter perylene-3,4,9,10-tetracarboxylic acid tetrapotassium salt (PTAS) for MoS2 seeds on the graphene surface. Mostly single or bilayer MoS2 flakes are grown on graphene with negligible defects even after the ozone treatment and the high-temperature growth process (up to 650 °C). Efficient charge transfer in the grown heterostructures is observed in the photoluminescence and photoresponses of devices based on the heterostructures.
Keywords: Area growths; Bi-layer; High quality; High-temperature growth; Nucleation control; Ozone treatment; Perylenes; Photoresponses; Chemical vapor deposition; Graphene; Heterostructure; MoS2